Analisis Pengaruh Kebijakan Lokasi dan Kebijakan Produk terhadap Kepuasan Penggunaan Jasa Percetakan Sua Grafika Padangsidimpuan - Lubis, Rizky Mery Octavianna; Pathuansyah, Yusuf; Nursalamah, Nursalamah (PT. Riset Press International, 2023)
uence of location and product policies on the decision to use the Sua Graphics Printing service in Padangsidimpuan, and to find out the most dominant factors influencing the decision to use printing services using the Sua Graphics Padangsidimpuan printing service. The hypothesis in this research is that location policy and product policy have a positive and significant effect on the decision to use Sua Graphics Padangsidimpuan printing services. The population and sample for this study were 30 employees. To obtain the required data, documentation techniques and questionnaires were used as data sources. The data obtained was then analyzed quantitatively using the multiple linear regression formula. The results of this research are that there is a positive and significant influence between the Location Policy provided by Sua Graphic Printing on the Decision to Use Sua Graphic Printing Services in Padangsidimpuan. Then there is a positive and significant influence between Product Policy on the Decision to Use Sua Graphics Printing Services in Padangsidimpuan.